Pemodelan Text Mining untuk Analisis Sentimen Terhadap Program Makan Siang Gratis di Media Sosial X Menggunakan Algoritma Support Vector Machine (SVM) - Purwanti, Zahra; Sugiyono (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The free lunch program is an initiative that provides free lunches and milk in schools and Islamic boarding schools, as well as providing nutritional support for children under five and pregnant women. Even though efforts to overcome stunting with this program are considered too late, providing free milk to pregnant women is considered more relevant for dealing with the stunting problem. Based on experience from various countries, the free lunch program shows various positive impacts, including increasing children's nutritional intake, increasing school participation, developing student character, and supporting the family and national economy. Discussions about this program received various responses from netizens, including platform X users. Online platforms have an important role in reaching and disseminating information about various social programs. In this context, the support vector machine method can be used to classify netizen responses to the free lunch program into positive and negative categories. It is hoped that this analysis will provide a deeper understanding of how this program is received by the general public, as well as provide suggestions for policy makers in designing social programs in the future.